Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$(b^2 - c^2)\cot A + (c^2 - a^2)\cot B + (a^2 -b^2)\cot C=0$$

I want this equation to be in the Sine form.

Please help me with steps.

Thanks a lot

share|cite|improve this question

Assuming that $a,b,c$ are the sides of a Triangle

Using Law of sines $$T=(b^2-c^2)\cot A=4R^2(\sin^2B-\sin^2C)\frac{\cos A}{\sin A}$$

Again using Prove $ \sin(A+B)\sin(A-B)=\sin^2A-\sin^2B $ or Prove that $\sin^2(A) - \sin^2(B) = \sin(A + B)\sin(A -B)$


But as $A+B+C=\pi$ and $\displaystyle\sin(\pi-x)=\sin x,\sin(B+C)=\sin(\pi-A)=\sin A$

$T$ becomes $\displaystyle 4R^2\sin A\sin(B-C)\frac{\cos A}{\sin A}$

As $\sin(B+C)=\sin A\ne0$ and $\cos(\pi-y)=-\cos y$

$T$ reduces to $\displaystyle 4R^2\sin(B-C)\{-\cos(B+C)\}=-2R^2\{2\sin(B-C)\cos(B+C)\}$

Using $\displaystyle2\sin B\cos A=\sin(A+B)-\sin(A-B), T=-2R^2(\underbrace{\sin2B-\sin2C}) $

share|cite|improve this answer
@NeelBhasin, another way:… – lab bhattacharjee Dec 25 '13 at 13:09

Another way: Group the cotangent ratios

Considering one of them

$\displaystyle T_1=b^2(\cot A-\cot C)=\frac{b^2\sin(C-A)}{\sin A\sin C}$

As $\sin B=\sin\{\pi-(C+A)\}=\sin(C+A)$ and $\sin B\ne0$(why?)

$\displaystyle T_1=\frac{b^2\sin(C-A)\sin(C+A)}{\sin A\sin C\sin B}$

Using $\sin(x+y)\sin(x-y)$ formula(mentioned in the other answer)

$\displaystyle T_1=\frac{b^2(\sin^2C-\sin^2A)}{\sin A\sin C\sin B}\ \ \ \ (1)$

Now using sine Law, $\displaystyle \frac c{\sin C}=\frac b{\sin B}=2R$ where $R$ is the circum-radius

Set the values of $\sin C,\sin A$ in the numerator of $(1)$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.